1974
DOI: 10.1210/endo-95-6-1711
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Interrelationships Among Circulating Levels of Estradiol, Progesterone and LH During the Rat Estrous Cycle: Effects of Exogenous Progesterone1

Abstract: Serum progesterone (P) levels display a circadian rhythm of varying amplitude during the estrous cycle. This rhythm is characterized by lowest levels of the day around noon and maximal levels at 1600 or 2300 hr. Amplitude was smallest on estrus and progressively greater on diestrus II, diestrus I and proestrus. Serum estradiol (E 2 ) concentrations declined gradually through estrus till 0800 hr of diestrus I. Thereafter, levels increased rapidly to peak at noon, and returned later to near nadir at 2300 hr of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
72
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 19 publications
15
72
0
Order By: Relevance
“…As previously reported oestradiol levels vary through the cycle with peak levels in pro-oestrus and lower levels at the other stages [30, 31]. Oestradiol levels at pro-oestrus were significantly higher than at di-oestrus (140.31 ± 11.29 pmol/l pro-oestrus versus 104.13 ± 19.94 pmol/l di-oestrus, p < 0.05).…”
Section: Resultssupporting
confidence: 62%
“…As previously reported oestradiol levels vary through the cycle with peak levels in pro-oestrus and lower levels at the other stages [30, 31]. Oestradiol levels at pro-oestrus were significantly higher than at di-oestrus (140.31 ± 11.29 pmol/l pro-oestrus versus 104.13 ± 19.94 pmol/l di-oestrus, p < 0.05).…”
Section: Resultssupporting
confidence: 62%
“…Hence, we suspect that a factor other than endotoxin extends diestrus. Kalra et al [11] and Kaneko et al [12] reported that the administration of progesterone to rats at proestrus inhibited the secretion of estrogen, which triggers the ovulatory LH surge, and prevented ovulation. As P 4 concentration was high, with a two to three fold increase in peak concentration compared to control rats on the day following infusion, we assume that the inoculation into the uterus stimulated progesterone secretion and suppressed ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…During diestrous 1 (Di 1) systemic levels of estrogen, prolactin (PRL), and the gonadotropins luteinizing hormone (LH) and follicle-sumulating honnone (FSH) are low (Kalra and Kalra, 1974). Plasma progesterone levels are slightly clevated, produced by corpora lutea ceUs of the ovary.…”
Section: Estrous Cyclementioning
confidence: 99%
“…It has been shown that progesterone secretion from the corpora lutea acts locally 10 limit follicular secretion of estrogen. Injecting progesterone into animaIs on Di II, thus preventing a faU in progesterone circulaLng levels, delays the onset of ovulation (KaIra and Kalra, 1974), while administration of progesterone antisera advances the onset of ovulation (Kaneko et aL, 1986). In the Long-Evans rat the extended life of the corpora luteum is observed by higher levels of progesterone during Di II.…”
Section: Estrous Cyclementioning
confidence: 99%